Development of the regional water balance regulation concept based on the geosystem approach - Anatoliy A. Yamashkin; Stanislav A. Yamashkin; Milan M. Radovanovic; Natalia S. Muchkaeva; Inna S. Lyamzina (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The article is devoted to solving the scientific problem of the regional water balance regulation concept development. The authors have proposed a methodology for solving the problem of the scarcity of labeled spatial data, based on the geosystem approach. A deep neural network model for the analysis of the geosystem model of the territory is proposed. An approach to the formation of ensembles of classifiers to improve the accuracy of the classification of spatial data is described. It is proved that the hierarchical structuring of geosystems optimizes diagnostics of the leading agents of physical and geographical factors interaction, patterns of spatio-temporal changes in their states, direction of metabolic processes and transformation of matter and energy development. Studies have shown that the combination of factors variety in the water balance formation forms many types of water resources conditions formation.